Tropical idolatry : a theological history of Catholic colonialism in the Pacific world, 1568-1700 - Green, R. L., 1978- (Lexington Books, 2018)
Tropical Idolatry examines how thinkers within the Society of Jesus attempted to convert Indigenous peoples of New Spain, the Philippine Islands, and the Mariana Islands to Catholicism. This book demonstrates the importance that both religious and political beliefs played in the establishment of the Church in the Spanish Pacific world.